Mechanisms of Radiation Bystander and Non-Targeted Effects: Implications to Radiation Carcinogenesis and Radiotherapy - Yahyapour, Rasoul; Motevaseli, Elahe; Rezaeyan, Abolhasan; Abdollahi, Hamid; Farhood, Bagher; Cheki, Mohsen; Najafi, Masoud; Villa, Vilmar (Current Radiopharmaceuticals, 2018)
Background: Knowledge of radiobiology is of paramount importance to be able to grasp and have an in-depth understanding of the consequences of ionizing radiation. One of the most important effects of this physical stressor's interaction to targeted and non-targeted cells, tissues and organs is on the late effects on the development of primary and secondary cancers. Thus, an in-depth understanding of the mechanisms of radiation carcinogenesis remains to be elucidated, and some studies have demonstrated or proposed a role of non-targeted effect in excess risk of cancer incidence. The non-targeted effect in radiobiology refers to a dynamic complex response in non-irradiated tissues caused by the release of presumably of clastogenic factors from irradiated cells. Although, most of these responses in non-targeted tissues have marked similarities to irradiated tissues, other studies have shown some differences. Also, the non-targeted effect has shown sex and tissue specificity that are seen in irradiated tissues too. So far, several studies have been conducted to depict mechanisms that may be involved in this phenomenon. Epigenetic dysfunctions, DNA damage and cell death are responsible for initiation of several signaling pathways that finally result in secretion of clastogenic factors. Moreover, studies have shown that damage to both nucleus and mitochondrial DNA, membrane and some organelles is involved. Oxidized DNA associated with other cell death factors stimulates secretion of inflammatory as well as some anti-inflammatory cytokines from irradiated area. Additionally, oxidative stress that results in damage to cellular structures to include cell membranes can affect secretion of exosomes and miRNAs. These bystander effect exogenous mediators migrate to distant tissues and stimulate various signaling pathways which can lead to changes in immune responses, epigenetic modulations and radiation carcinogenesis. Conclusion: In this review, we focus on descriptive and hierarchical events with emphasis on the molecular and functional interactions of ionizing radiation with cells to the mechanisms involved in cancer induction in non-targeted tissues.
Keywords: DNA damage